The UP Diliman response to the COVID-19 pandemic - Pacia, Adeline A. (Social Science Diliman: A Philippine Journal of Society and Change, 2021)
As the national university, the University of the Philippines is mandated to perform its unique and distinctive leadership in higher education and development. As the main campus, UP Diliman (UPD) has thus taken the lead in setting academic standards and initiating innovations in teaching, research, and faculty development. As the flagship campus of the national university, UPD also took the lead in responding to the challenges of the COVID-19 pandemic. Its COVID-19 Response Framework shows the different areas of the University’s response to minimize the socio-economic impact of COVID-19 on the UPD community. The four major areas of the Response Framework include ensuring good health and safety, ensuring adequate and continuous flow of UPD services, supporting academic and research activities, and promoting effective communications. The Response Framework is designed for the short- to mid-term period to address the COVID-19 pandemic. However, it may be updated to provide long-term response as we transition to the “next normal.”
Keywords: University of the Philippines; UP Diliman; COVID-19; response framework